PROGRAM MUSHOLLA CERDAS DALAM UPAYA MENINGKATKAN PARTISIPASI WARGA UNTUK BERKEGIATAN DI TEMPAT IBADAH - Diki Arisandi; Luluk Elvitaria; Radi Syafirman; Yeni Dwi Fahlufi; Yulia Darma Yanti; Sarah Fadila (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2023)
Musholla or surau is a place that resembles a mosque with a smaller form and often used as a place for religious activities, such as congregational prayers, reciting the Koran, and various religious activities for Muslims. This community service activity was held in Buluh Cina Village, which is a Tourism Village in Kampar Regency, Riau Province. One of the musholla in the village is the Musholla Al-Aqsa. When the service team conducted an initial survey, the condition of the musholla was deserted and there was a shortage of teaching staff and musholla managers, even though the musholla was in the middle of the village and was always passed by residents and travelers. Based on this situation analysis, the service team created assistance activities for residents, namely the smart musholla program which aimed to increase residents' participation in enlivening the musholla. The programs that have been carried out including maghrib recitation, five daily prayers in congregation, dawn prayer studies, Isha studies, evening goro, and musholla management. The service team carried out this activity for one month, and based on observations before and after the activity, there was an increase in the participation rate of residents of various ages in enlivening the Musholla Al-Aqsa.